2012
DOI: 10.2190/cs.13.4.c
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Students' Personality Traits and Psychosocial Characteristics with Academic Retention

Abstract: This study investigated whether academic non-achievers differed from academic achievers in terms of their personal characteristics. A sample of 216 undergraduate students that were either enrolled in a college restoration program or part of a control group were administered the 16PF-5 Personality Questionnaire (Cattell, Cattell, & Cattell, 1993) and the College Student Questionnaire measuring five psychosocial factors. MANOVAs and independent t-tests revealed significant group differences for six of the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Lastly, low self-control failed to associate with academic expectations. Again, this finding is consistent with the literature that explains there is a difference between academically high and low achieving students in terms of low self-control (Munt & Merydith, 2012). In contrast, in the case of our study, we examined the relationship between low self-control and academically associated expectations, and not academic achievement outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lastly, low self-control failed to associate with academic expectations. Again, this finding is consistent with the literature that explains there is a difference between academically high and low achieving students in terms of low self-control (Munt & Merydith, 2012). In contrast, in the case of our study, we examined the relationship between low self-control and academically associated expectations, and not academic achievement outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Scholars commonly differentiate between higher levels and lower levels of self-control such that those individuals having higher self-control achieve positive outcomes such as more academic success (de Ridder et al, 2012;Tangney et al, 2004). Stated differently, there is a statistically meaningful difference between high performing and low performing students on the measure of low self-control (Munt & Merydith, 2012). For example, Duckworth and Seligman (2005) examined eighth grade students over time and determined that self-control was more influential over grades than was intelligence (IQ).…”
Section: The Role Of Low Self-controlmentioning
confidence: 99%
“…A few other studies, however, relied on more rigorous research designs than did the above examples. Bettinger and Baker (2014) conducted a randomized controlled trial to estimate the effects of student coaching on retention; Schnell and Doetkott (2003) used propensity score matching to evaluate the impact of first-year seminars on retention; and Munt and Merydith (2012) used the instrumental variable estimation to explore the connections among personality traits, psychological characteristics, and retention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence the first aim of this study was to investigate how well the Big Five personality factors predict time management behaviour dimensions in a broader sample. Previous theoretical and empirical research (Douglas et al, 2016;Feig, 1995;Liu et al, 2009;Munt & Merydith, 2012;Mohall & Najafzadeh, 2015) suggested that, of the Big Five, conscientiousness would be the best predictor of time management and would be positively correlated with all aspects of time management behaviour. People higher in Conscientiousness should be better at setting goals and priorities, better at scheduling and planning, have a stronger preference for organisation, and hence perceive themselves to have greater control over their time.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…Some of the studies dealt with personality variables and time management. Munt and Merydith (2012) explored the relationship between Cattell's 16 personality factors and time management in college students and found that time management was positively correlated with emotional stability, rule consciousness, perfectionism, and self-control and negatively correlated with abstractedness and anxiety. Liu, Rijmen, MacCann, and Roberts (2009) researched relationships between Big Five dimensions and time management (assessed using their own instrument) in middle-school students and found that Conscientiousness, Agreeableness, and Openness were positively correlated with time management and negatively correlated with Neuroticism.…”
mentioning
confidence: 99%